2014
DOI: 10.1002/2013jf003069
|View full text |Cite
|
Sign up to set email alerts
|

Inundation of a barrier island (Chandeleur Islands, Louisiana, USA) during a hurricane: Observed water‐level gradients and modeled seaward sand transport

Abstract: Large geomorphic changes to barrier islands may occur during inundation, when storm surge exceeds island elevation. Inundation occurs episodically and under energetic conditions that make quantitative observations difficult. We measured water levels on both sides of a barrier island in the northern Chandeleur Islands during inundation by Hurricane Isaac. Wind patterns caused the water levels to slope from the bay side to the ocean side for much of the storm. Modeled geomorphic changes during the storm were ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 83 publications
5
59
0
Order By: Relevance
“…Large‐scale and local pressure gradients can oppose each other at times (Engelstad et al, ). Further, higher water levels in the back‐barrier basin than on the ocean side were observed to generate seaward flows (Engelstad et al, ; Hoekstra et al, ; Sherwood et al, ), which was also found in modeling studies (Harter & Figlus, ; Sherwood et al, ; Wesselman et al, ). In a combined observation‐modeling study of barrier island inundation in the Gulf of Mexico, Sherwood et al () found that the seaward directed water level gradient resulted in the deposition of a significant amount of sediment on the ocean side.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Large‐scale and local pressure gradients can oppose each other at times (Engelstad et al, ). Further, higher water levels in the back‐barrier basin than on the ocean side were observed to generate seaward flows (Engelstad et al, ; Hoekstra et al, ; Sherwood et al, ), which was also found in modeling studies (Harter & Figlus, ; Sherwood et al, ; Wesselman et al, ). In a combined observation‐modeling study of barrier island inundation in the Gulf of Mexico, Sherwood et al () found that the seaward directed water level gradient resulted in the deposition of a significant amount of sediment on the ocean side.…”
Section: Introductionmentioning
confidence: 72%
“…Further, higher water levels in the back‐barrier basin than on the ocean side were observed to generate seaward flows (Engelstad et al, ; Hoekstra et al, ; Sherwood et al, ), which was also found in modeling studies (Harter & Figlus, ; Sherwood et al, ; Wesselman et al, ). In a combined observation‐modeling study of barrier island inundation in the Gulf of Mexico, Sherwood et al () found that the seaward directed water level gradient resulted in the deposition of a significant amount of sediment on the ocean side. A modeling study by McCall et al () suggested that higher water levels in the back‐barrier relative to the surge levels in the ocean increased back‐barrier deposition and reduced deposition in the basin due to a decrease in flow velocity.…”
Section: Introductionmentioning
confidence: 72%
“…Sherwood et al. () also found reversed currents as a result of higher back‐barrier water levels for the Chandeleur Islands in Louisiana, while Hoekstra et al. () concluded as well that water can reach Schiermonnikoog from both sides of the island.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Sherwood et al. , ). The short waves (<20 s) move to the shore in wave groups, creating infragravity (IG) waves with a period of 20–200 s (Battjes, ; Herbers et al.…”
Section: Introductionmentioning
confidence: 99%
“…Just as important as understanding the potential for on--or offshore sediment transport between the upper and lower shoreface (Aagaard, 2014) is an understanding of how changes in the upper shoreface are morphologically communicated offshore. The myriad processes that can change coastlines, from overwash (Donnelly et al, 2006;Sherwood et al, 2014) to alongshore sediment transport gradients (Ashton and Murray, 2006a) or even human activities such as beach nourishment (Jin et al, 2013), motivate a better understanding of how the shoreface behaves as a morphologic unit. The focus of this study is the development of a formulation for the long--term morphodynamic evolution of a sandy wave--dominated shoreface.…”
Section: Introductionmentioning
confidence: 99%